Subsurface Temperature Estimation during Traction Transmission in the Variator of Metal V-Belt CVTs - Yuki Ono (Japanese Society of Tribologists, 2020)
This paper evaluates a temperature variation between pulley sheaves and a metal push belt of an automotive Continuously Variable Transmission (CVT). In a study of wear mechanisms on pulley sheaves, one of the authors previously demonstrated a crystallographic phase transition from body-centered cubic (BCC) to face-centered cubic (FCC) in fine grains beneath a sliding surface of a pulley sheave which had been operated for certain period of time. Although prevailing metallurgy indicates that the transition needs a thermal history over the eutectoid point of the material, surface temperature on pulley sheaves have not been evaluated or reported. The authors therefore analyzed temperature variation on the pulley sheave under a same operating condition of the CVT as that the phase transition was discovered. The major technical problem was measurement methods used to obtain temperature distribution on the pulley surface where the clamp position of the V-belt changes continuously according to transmission ratios of the CVT. Uniquely developed infrared borescope enabled non-contact temperature measurements near the contact area during CVT operation. Measurement results were introduced to numerical calculation to predict the highest temperature on the power transmission area including subsurface area. The resultant highest temperature did not reach the eutectoid point of the material and indicated that single source of thermal energy did not occur in abovementioned phase transition. The findings generated our hypothesis that combination of energy sources, such as thermal dissipation due to power transmission, repeated impulsive forces due to contact and friction, and consequent generation of finer grain structure, enhances the phase transformation from BCC to FCC even under milder conditions than the thresholds of every single energy source.